Heart Rate Variability Analysis in Risk of Asthma Stratification - Milagro, Javier; Gil, Eduardo; Lázaro, Jesús; Seppä, Ville-Pekka; Pekka Malmberg, L.; Pelkonen, Anna S.; Kotaniemi-Syrjänen, Anne; Makelä, Mika J.; Viik, Jari; Bailón, Raquel (Jornada de Jóvenes Investigadores del I3A, 2017)
Early diagnosis of asthma is crucial to avoid long-term effects such as permanent airway obstruction. Pathogenesis of asthma has been related with autonomic nervous system (ANS) dysfunction, concretely with abnormal parasympathetic activity. As heart rate variability (HRV) analysis does reflect ANS activity, it has been employed here in risk of asthma stratification.